Mentoring for Senior Preclinical Medical Students in a Faculty of Medicine - Elisabeth Rukmini; Natalia Puspadewi; Nurul Hariadi (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Background: Universities’ core values need to be translated into real learning design. At the end of the preclinical phase, the curriculum turned into a more comprehensive and full of trustworthiness of knowledge and attitudes. Meanwhile, the development of attitudes requires intensive support (mentoring). The team intended to translate the core values of Atma Jaya (Christianity, Excellence, Professional, Caring, KUPP) into an instructional design. Mentoring was the selected approach to build a dialogue and work together with students. In this article we presented the implementation of mentoring on the Elective Block of Medical Education (Block IPK) for the 7th semester medical students at Atma Jaya School of Medicine (August-September 2015, 5 weeks). The Block IPK then was followed by an advanced mentoring until the end of November 2015. We intended to realise KUPP through mentorship throughout Block IPK until the end of the first semester of 2015/2016. In particular, this action research was intended to find answers to research questions: (1) What were perceived by the students throughout the mentoring in the Block IPK ?, (2) What were perceived by the students throughout the mentoring after Block IPK?, (3) What products were the students proud of after the mentoring?Method: Qualitative analysis using Delphi method were utilized to determine the main theme. Analyses were fulfilled using interpretive analysis. Data were taken from: reflective writing, FGD or interviews, email communication, and the mentors’ observation. The Delphi was performed in three rounds.  Results: Findings showed positive impression on Block IPK. Students were aware of the meaning or significance of Block IPK. Field trip and working group were learning methods which considered to be important, because the methods had succeeded in generating meaningful learning for students. Approximately 40-50% of the students stated the significance of working group in Block IPK. Approximately 50-75% of students experienced personal cultivation. Approximately 67-75% of the class stated the superiority of Blok IPK and mentoring. Students appreciated the working group, which gave opportunities to have a discussion on campus with mentors. Mentoring had advantages in terms of students’ cultivation of the freedom of thought and to proceed further learning (advance learning).Conclusion: Students perceived positively to mentoring activities during and after the Block IPK. Mentoring benefited to personal cultivation, academic support, role modeling and leadership. The implication to medical education institutions was to implement a mentoring steadily.